The effects of alcohol on recovery from musculoskeletal trauma and injuries - Shahrzad Bazargan-Hejazi; Vincent Arriola; Daniel Arriola; Deyu Pan; Kaveh Dehghan; Emad Alamoutifard; Elby Washington (BioSocial Health Journal)
Introduction: This study aimed to investigate the association between alcohol misuse (abuse and dependence) and clinical outcomes including infection, length of stay (LOS), and in-hospital mortality (IHM) among patients with musculoskeletal injuries. Methods: A retrospective analysis was conducted using California Hospital Discharge Data for 2018. The study included patients aged 18 years or older with musculoskeletal injuries categorized by injury sites (head/neck, trunk, and extremities) and alcohol misuse (abuse or dependence). Multivariate logistic regression analysis was used to assess the independent association of alcohol misuse with the outcome variables, controlling for age, gender, ethnicity, and insurance status. Results: Among 3.7 million discharges, 207623 (40.2%) had alcohol abuse, and 58.8% had alcohol dependence. The findings revealed that among musculoskeletal injury discharges, those with alcohol abuse, compared to alcohol dependence, had higher odds of infection (OR=1.25; CI=1.07-1.45). However, they had lower odds of LOS of≥4 days (OR=0.78; CI=0.77-0.79), and lower odds of IHM (OR=0.91; CI=0.86-0.96). Extremity injuries were associated with higher odds of infection, longer hospital stays, and lower IHM compared to head/neck and trunk injuries. Males compared to females and patients aged 67 or older compared to their 18-34 age group encounters were more likely to experience infection, LOS of≥4 days, and IHM. Hispanic and Asian patients experienced less infection and fewer days in the hospital but presented with higher odds of IHM. Conclusion: Our results reveal the burden of alcohol misuse in treatment outcomes among patients undergoing hospitalization for treatment of musculoskeletal injuries as they related to infection, length of hospital stay, and IHM. These findings also highlight the potential economic implications of alcohol-related musculoskeletal injuries. Our findings emphasize the necessity for an approach that goes beyond treating immediate physical injury, but considering a patient’s history of alcohol abuse and providing appropriate support and interventions to improve treatment outcomes for individuals affected by musculoskeletal injuries and alcohol misuse.